Evaluation of Healing Effect of Stromal Vascular Fraction and Platelet Rich Plasma Application on Ulcerative Ear Wound in Diabetic Rabbit (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
A debilitating complication of diabetes mellitus is diabetic ulcers, which leads to increased overall morbidity in patients. The high growth factor content in Platelet Rich Plasma (PRP) makes it a widely used intervention for the treatment of diabetic foot ulcers. The topical application of Stromal Vascular Fraction (SVF) could possibly enhance wound healing. This study aims at evaluating the efficacy of combining SVF and PRP on wound healing in diabetic rabbit model. Diabetes was induced in New Zealand white rabbits by intravenous injection of 125 mg/Kg Alloxan. After two weeks of alloxan, three 6 mm diameter, full thickness excision wounds were made, on inner side of the right ear pinna. The animals after induction were allocated into 4 groups with [8 Diabetic (treated with SVF+PRP), 4 Diabetic (treated with 10% Povidone Iodine (PI)), 1 non-diabetic (treated with SVF+PRP), 1 non diabetic (treated with 10% PI)]. The effect of combined therapy was evaluated by assessing wound margin closure rate, histo-pathological evaluation, and inflammatory cell infiltration, epithelization of ulcerative region, neo-vascularization, and fibrosis. We observed that the rate of wound closure is enhanced in wounds treated with SVF+PRP as compared to the PI solution. Wound closure and healthy healing were demonstrated by histo-pathological analysis. The analysis clearly indicates that the healing process of PI treated animals is slower than that of SVF + PRP treated animals. In conclusion, based on wound healing assessment and histo-pathological examination, the diabetic rabbits treated with SVF + PRP exhibited early development of granulation tissue and early signs of wound closure as compared to diabetic animals with normal PI dressing.